Generic and police-specific occupational risk factors of mental health and well-being among urban and sub-urban Malaysian traffic police officers - Rasdi, Irniza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Mental health in policing has been widely studied but incidence of mental health illnesses among them keep increasing. This study aimed to analyse generic and specific work stressors among police officers and their differences between urban and sub-urban police population. Methods: This was a cross-sectional study conducted in Kuala Lumpur and in nine sub-urban provinces in Pahang and Negeri Sembilan which involved 328 traffic police officers recruited by universal sampling. Data was collected by using self-administered questionnaire consisted of Police Stress Questionnaire (PSQ), the Job Content Questionnaire (JCQ), the Work Family Conflicts (WFC), the International Union against Tuberculosis and Lung Disease (IUATLD), and the General Health Questionnaire (GHQ-12). Results: The response rate was 71.30%. Majority of respondents were male (86.59%) with average age of 38.84 years old. The prevalence of probable mental health illnesses was 29.80% in sub-urban and 44.30% in urban. Job demand, role ambiguity, family to work conflicts and almost all specific works stressors were significantly higher among urban respondents. For urban, results showed that the most significant stressor was perceived air pollution (p<0.01) followed by age (p=0.01), job control (p=0.01), and operational stressors (p=0.03). While in sub-urban, the most significant stressors determined were the presence of chronic diseases (p=0.03) and organizational stressors (p=0.01). Conclusion: The prevalence of probable mental health illnesses was high in both study areas and each area had its own unique work stressors. Intervention strategies prioritizing on these factors are therefore recommended.